Mechanochemical changes in absorption and fluorescence of DDM-containing epoxies. (25th April 2018) - Toivola, Ryan; Jang, Sei-Hum; Mannikko, Donald; Stoll, Stefan; Jen, Alex K-Y.; Flinn, Brian D.
Abstract: Mechanochemical changes in absorption or fluorescence in solid polymers are important for the development of new methods of damage sensing, and must be demonstrated in structural polymers such as epoxies for widespread use. With this in mind, we have observed that diamine-cured epoxies containing 4, 4′-diaminodiphenyl methane (DDM) framework display mechanochemical changes in both absorption and fluorescence. Samples change from original "blue" to mechanochemically activated "red" fluorescence in response to uniaxial compressive deformation beginning in the early stages of strain hardening. Accompanying the "red" fluorescence is an increase in radical concentration; both are impermanent in time, suggesting the reactive intermediate as the fluorophore. Orange and green chromophores are generated by compression as well; the orange chromophore is the red-emitting fluorophore while the green chromophore is non-fluorescent at ambient conditions. Our work indicates that the DDM structure is the origin of the mechanochromic responses, and stoichiometric variation and degree of cure are strong determinants for whether orange or green chromophores will form. Based on these results the red-emitting orange chromophore is proposed as a reactive radical intermediate of core DDM structure, generated by bond scission reactions on the epoxy network. The green chromophore is a quinoidal methine resulting from the intermediates. Graphical abstract: Image 1 Highlights: Diaminodiphenylmethane (DDM) containing epoxies show a "blue-to-red" change in fluorescent emission in response to uniaxial compression. The onset of the "blue-to-red" change occurs in the strain hardening region, associated with bond scission. Mechanochromic formation of orange (benzoidal DDM radical) and green (quinoidal methine) chromophores also observed. Stoichiometry and degree of cure changes in a formulation can determine which chromophores are formed via mechanochromism.